Performance test of private cloud Cloudstack / Mohd Izainezazmi Abd Azis - Abd Azis, Mohd Izainezazmi (2014)
At present, cloud computing technology and its services have been increasingly improved, but its application for small and medium ( SME ) in Malaysia is just the beginning. Therefore to many cloud management system creates a confuse for the cloud user to choose the software based on their business needed. This paper develops cloud architecture using open source platforms which is CloudStack. The performance and features of virtual machines (VMs) initiated and managed by CloudStack are test in terms of CPU utilization, I/O disk Speed,network performance using suitable benchmarks then analyze the result.